Hadith #2535 - Sunan Abi Dawud - Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Mas'ud; Mrh al-Hmdany Akhrj al-Bghwy; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent us on foot to get spoil, but we returned without getting any. When he saw the signs of distress on our faces, he stood up on our faces and said: O Allah, do not put them under my care, for I would be too weak to care for them; do not put them in care of themselves, for they would be incapable of that, and do not put them in the care of men, for they would choose the best things for themselves. He then placed his hand on my head and said: Ibn Hawalah, when you se
Grade: Sahih

Hadith #181 - Jami' al-Tirmidhi - Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; ibn Mas'ud; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Mrh al-Hmdany Akhrj al-Bghwy; Muhammad bin Talha bin Masraf محمد بن طلحة بن مصرف; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي; Zubayd bin al-Harith زبيد بن الحارث اليامي (Jami' al-Tirmidhi)
Allah’s Messenger said: “Salatul-Wusta is the Asr prayer.”
Grade:

Hadith #1782 - Jami' al-Tirmidhi - Abu Musa al-Asha'ari; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Mrh al-Hmdany Akhrj al-Bghwy; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Jami' al-Tirmidhi)
“The Messenger of Allah (ﷺ) prohibited that a man should put on sandals while he is standing.” This Hadith is Hasan Gharib. ‘Ubaidullah bin ‘Amr Ar-Raqqi reported this Hadith from Ma’mar, from Qatadah, from Anas. Both of the Ahadith are not correct according to the people of Hadith. Al-Harith bin Nabhan is not a Hafiz according to them, and we do not know any basis for the narration of Qatadah from Anas.
Grade:

Hadith #2575 - Jami' al-Tirmidhi - Aban bin Ishaq al-Asady أبان بن إسحاق الأسدي; ibn Mas'ud; Mrh al-Hmdany Akhrj al-Bghwy; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Yahya bin Musa Khat يحيى بن موسى خت (Jami' al-Tirmidhi)
“As-Saud is a mountain in the Fire, a disbeliever will be raised upon it for seventy autumns and then similarly he will fall down it, forever.” (Daif)
Grade:

Hadith #3172 - Jami' al-Tirmidhi - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; ibn Mas'ud; Mrh al-Hmdany Akhrj al-Bghwy (Jami' al-Tirmidhi)
“When the Prophet (ﷺ) was expelled from Makkah a man said: ‘They have driven out their Prophet’ so (the following) was revealed: “Permission (to fight) is given to those who are fought against, because they have been wronged; and surely, Allah is able to give them victory. Those who have been expelled from their homes unjustly (22:39).”
Grade:

Hadith #3369 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Isma'il bin 'Abdur Rahman al-Saddi إسماعيل بن عبد الرحمن السدي; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Mrh al-Hmdany Akhrj al-Bghwy; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام (Jami' al-Tirmidhi)
The Prophet said: “There is nothing more honorable with Allah than supplication.”
Grade:

Hadith #3403 - Sunan Ibn Majah - Abu Musa al-Asha'ari; Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Mrh al-Hmdany Akhrj al-Bghwy; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
“Whoever has three daughters and is patient towards them, and feeds them, gives them to drink, and clothes them from his wealth; they will be a shield for him from the Fire on the Day of Resurrection.'”
Grade: